Metabolic Hormone Profiles in Breast Milk From Mothers of Moderate-Late Preterm Infants Are Associated With Growth From Birth to 4 Months in a Sex-Specific Manner - Galante, Laura; Reynolds, Clare M.; Milan, Amber M.; Alexander, Tanith; Bloomfield, Frank H.; Jiang, Yannan; Asadi, Sharin; Muelbert, Mariana; Cameron-Smith, David; Pundir, Shikha; Vickers, Mark H.; , the DIAMOND study team (Frontiers in Nutrition, 2021)
Background: Differing environmental conditions experienced by mother-infant dyads may influence composition of the milk received by the infant. As a consequence, diverse milk compositional profiles may contribute to different postnatal outcomes, especially in infants facing adverse perinatal environments. We investigated whether variability in milk concentrations of key metabolic hormones is associated with different growth outcomes in infants born preterm, a perinatal complication known to impact on infant growth. Methods: Human milk samples were collected from 169 mothers of 191 infants enrolled in the DIAMOND trial, a randomized trial of nutrition for moderate-late preterm infants, at 5 and 10 days postpartum and again at 4 months’ corrected age and analysed for leptin, adiponectin and insulin-like growth factor (IGF)-1. Infant weight and body composition were measured at birth, discharge and 4 months’ corrected age. Multiple linear regression models were used to examine correlations between milk hormone concentrations, weight z-scores and body composition at discharge and 4 months’ corrected age, and weight gain from birth to 4 months’ corrected age. Sex-specific interactions were examined. Results: Higher milk IGF-1 concentrations on day 5 after birth were associated with greater infant fat-free mass at 4 months’ corrected age. Milk IGF-1 concentrations at 4 months were positively associated with fat mass and fat-free mass at 4 months in boys but not girls. Milk leptin concentrations on day 5 after birth were positively associated with fat mass at discharge from hospital, but negatively associated with fat mass at 4 months’ corrected age. No significant association was found for milk adiponectin concentrations. Conclusion: Milk IGF-1 and leptin concentrations in mothers of moderate-late preterm babies are associated with different growth and body composition through to 4 months’ corrected age and these associations are often different in boys and girls. The sex-specific effects of nutrient and hormone exposure during early life in preterm infants warrants further investigation to optimise the nutritional care these infants receive, particularly in hospital, where the same nutrition is provided to boys and girls.